Postępowania związane z wykonywaniem kary ograniczenia wolności – aspekty instytucjonalne - Wiciński, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The study concerns the penalty of restriction of liberty, especially its amendment from 2015. This amendment was certainly the most important one during the validity period of the current codification, because it actually changed the place of the penalty of restriction of liberty in the structure of all penalties. This circumstance is also important from a dogmatic point of view, as there were — as has already been pointed out — views in the doctrine recognizing the penalty of restriction of liberty on the basis of medium level crimes as an “alternative” to the penalty of deprivation of liberty without a conditional suspension of its execution. It seems that from the perspective of Art. 58 § 1 of the Penal Code and the current penal policy, the discussed type of criminal punishment aspires to be perceived as a form of legal and criminal reaction consistent with the ordinary order of things in relation to crimes punishable by up to five years imprisonment.
Keywords: restriction of liberty; penal policy; socially useful work; community service